Pengaruh Pemanfaatan Teknologi dan Kualitas Pelayanan Terhadap Loyalitas Nasabah - Artanaya, I Made Dwi Darma; Deriani, Ni Wayan; Eni Sulistyawati, Ni Putu (UNHI Press, 2025)
Digitalization has almost changed many things in consumer purchasing decisions or choosing certain services that are demanded by consumers. Even this rapid technological development has caused changes in lifestyles that tend to want simple and easy. This is also felt by financial institutions including the Village Credit Institution (LPD). LPD is a financial institution owned by a Traditional Village that operates in the Traditional Village area so that the use of technology and service quality so that customers can transact more easily so that customer loyalty can be achieved in order to build LPD on an ongoing basis. This study aims to examine the effect of technology utilization and service quality on LPD customer loyalty. This research was conducted at the LPD located in Bedha Traditional Village Tabanan. The data collection method was carried out by distributing questionnaires using 4 Likert scales with the provision of respondent selection using random sampling method from savings, credit and deposit customers at LPD Desa Adat Bedha. Data analysis techniques in this study using multiple linear (SPSS). Based on data analysis that technology utilization and service quality have a positive impact on customer loyalty at the Bedha Traditional Village Credit Institution Tabanan.